Experience of intraoperative recurrent laryngeal nerve monitoring in a single center-normative recurrent laryngeal nerve electromyographic data - Soh G. (Jaypee Brothers Medical Publishers (P) Ltd, 2018)
10.5005/jp-journals-10002-1198